Comparing Singlet Oxygen Generation of Schiff Base Substituted Novel Silicon Phthalocyanines by Sonophotochemical and Photochemical Applications - Unlu, Seda; Atmaca, Goknur Yasa; Elmali, Fikriye Tuncel; Erdogmus, Ali (WILEY, 2023)
Although the sonophotodynamic method has an effective therapeutic outcome for anticancer treatment compared with the photodynamic method, there are not enough related studies in the literature and this study aims to contribute to the development of sonophotodynamic studies. For this purpose, the Schiff base substituted silicon phthalocyanines were designed and synthesized as effective sensitizer candidates and the photophysicochemical and sonophotochemical features of the phthalocyanines were examined to increase singlet oxygen efficiency. The calculated phi(Delta) values indicate that the contribution of substituent groups improved the production of singlet oxygen compared with silicon (IV) phthalocyanine dichloride (SiPcCI2) and also the sonophotochemical applications increased the singlet oxygen yields. The phi(A) values (phi(A) = 0.76 for axially bis-{4-[(E)-(pyridin-3-ylimino)methyl]phenol} substituted silicon (IV) phthalocyanine (2a), 0.68 for axially bis-4-[(E)-{[(pyridin-3-yl)methyl]imino}methyl]phenol substituted silicon (IV) phthalocyanine (2b) in photochemical study) reached to phi(A)= 0.98 for 2a, 0.94 for 2b in sonophotochemical study. This article will enrich the literature on increasing singlet oxygen yield.
Keywords: PHOTODYNAMIC THERAPY; BREAST-CANCER; COMPLEXES; ZINC; Biochemistry & Molecular Biology; Biophysics